Pengaruh Media Kahoot Terhadap Peningkatan Pembelajaran Maharah Istima’ di MTs Wali Songo Purwosari Pasuruan - Indzar Robiatul Adawiyah; Syarifuddin (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study entitled the influence of Kahoot media on increasing maharah istima' learning at MTs Wali Songo Purwosari Pasuruan. The purpose of this research is to find out how the application of Kahoot media affects the learning of maharah istima' for class VII students at MTs Wali Songo Sumberrejo Purwosari Pasuruan. In this case, the research method uses a quantitative approach and the form of the design is a one group pretest-posttest design. The object of this study was taken from the class VII population with a total of 192 students. While the sample was taken randomly using a random sampling technique with a total of 24 students. Data collection techniques were taken by tests. The validity of the instrument was tested using the validity and reliability tests with the help of the SPSS version 26 application. The results of the paired sample t-test of this study were a significance value of 0.000, which means that there is a significant effect between the application of Kahoot media to maharah istima' in class. VII MTs Wali Songo Sumberrejo Purwosari Pasuruan.